Molecular networks of pathogenicity control in Xanthomonas phaseoli pv. manihotis (2018)
Cassava (Manihot esculenta Crantz) is one the most important crops around the world due to its environmental resistance and industrial utility. Xanthomonas phaseoli pv. manihotis (Xpm) is the causal agent of the cassava bacterial blight, the main bacterial disease of cassava. In Xanthomonas, several studies have been performed in the fields of transcriptomics, metabolomics, population genetics, and phylogenetics. However, few studies of gene expression profiles for pathogens in planta have been performed in the Xanthomonas genus, or in other plant pathogens. Moreover, few studies have analyzed the pathogenic system as whole. Systems biology is a new interdisciplinary field that has allowed to investigate organisms as a whole, where the totality of the system is greater than the independent addition of the parts. The scope of this thesis is to study the molecular mechanisms involved in pathogenicity of Xpm both in vitro and in planta. The gene expression profiles of mutants of Xpm related with molecular mechanisms of pathogenicity were studied in vitro. Furthermore, the interaction between cassava and Xpm in planta was also studied using gene expression profiles. The thesis is divided in three chapters. The first chapter responds to the need of having an updated review of network biology in bacterial pathogens and how this field of systems biology can help to understand the molecular mechanism of plant-pathogen interactions. The second chapter presents the first metabolic model of Xpm, reconstructed at a genome-scale, revealing important features of Xpm related with pathogenicity, virulence and bacterial defense. The final chapter analyzes the gene expression profiles of Xpm in planta during the interaction with cassava